Professional Development Schools: Establishing Alliances to Bridge the Gap between Universities and Schools Escuelas de desarrollo profesional: creando alianzas para reducir la brecha entre colegios y universidades - Rocío Monguí Sánchez; Claudia Torres Jaramillo (Profile: Issues in Teachers' Professional Development)
This article narrates the way a Professional Development School (PDS) got started. PDSs refer to alliances among educational institutions that join forces and resources to provide community members high quality services and products. Two stages are depicted. The first one deals with the setting up of human and material resources, identifying ways of collaboration among institutions and defining the roles of every partner involved. The second stage has to do with the implementation of the proposal per se, the obstacles faced and the action plans to carry on with the implementation. Partial findings and outcomes of this PDS-in-progress are shared with the hope of promoting the PDS concept in our community by means of establishing more partnerships, receiving feedback from experienced peers, and establishing networks. Este artículo narra el proceso de implementación de una Escuela de Desarrollo Profesional (PDS). Las PDSs se entienden como alianzas entre instituciones educativas que unen fuerzas y recursos para brindar alta calidad y servicios a los miembros de la comunidad. La experiencia se presenta en dos etapas. La primera describe la organización de los recursos humanos y materiales, identificando formas de colaboración entre las instituciones involucradas y definiendo los roles de cada participante. En la segunda etapa se expone el desarrollo de la propuesta, los obstáculos que se enfrentaron y el plan de acción que se siguió. Se presentan los resultados obtenidos hasta el momento, en la perspectiva de promover el concepto de PDS en nuestra comunidad académica a través del establecimiento de más alianzas estratégicas, de la retroalimentación de colegas experimentados y redes de trabajo.